1996
DOI: 10.1007/s002280050163
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent inhibition of CYP1A2, CYP2C19 and CYP2D6 by citalopram, fluoxetine, fluvoxamine and paroxetine

Abstract: This investigation confirms that paroxetine and fluoxetine are potent inhibitors of CYP2D6, that fluvoxamine and fluoxetine are moderate inhibitors of CYP2C19 and that fluvoxamine is a potent inhibitor of CYP1A2 in humans in vivo. The clinical prediction of interaction from single-dose experiments may have to take the degree of accumulation during steady-state after multiple doses into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
137
0
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(153 citation statements)
references
References 36 publications
11
137
0
5
Order By: Relevance
“…In such cases, metabolite formation of a probe drug may be reduced, potentially changing an individual's apparent phenotype from an EM to a PM [15]. This phenomenon was demonstrated by Jeppesen et al [16] in a study involving a group of healthy volunteers identified as CYP2D6 EMs. In that study, participants received single oral doses of four selective serotonin reuptake inhibitor (SSRI) antidepressants that were known to be CYP2D6 inhibitors: citalopram (Celexa ® ; Forest Pharmaceuticals, Inc., St. Louis), fluoxetine (Prozac ® ; Eli Lilly and Company, Indianapolis), fluvoxamine, and paroxetine (Paxil ® ; GlaxoSmithKline, Philadelphia).…”
Section: Significance Of Cyp2d6 Polymorphismsmentioning
confidence: 92%
“…In such cases, metabolite formation of a probe drug may be reduced, potentially changing an individual's apparent phenotype from an EM to a PM [15]. This phenomenon was demonstrated by Jeppesen et al [16] in a study involving a group of healthy volunteers identified as CYP2D6 EMs. In that study, participants received single oral doses of four selective serotonin reuptake inhibitor (SSRI) antidepressants that were known to be CYP2D6 inhibitors: citalopram (Celexa ® ; Forest Pharmaceuticals, Inc., St. Louis), fluoxetine (Prozac ® ; Eli Lilly and Company, Indianapolis), fluvoxamine, and paroxetine (Paxil ® ; GlaxoSmithKline, Philadelphia).…”
Section: Significance Of Cyp2d6 Polymorphismsmentioning
confidence: 92%
“…The SSRIs are twice as effective as the "placebo" effect at reducing menopausal symptoms in randomized clinical trials [138][139][140], so there is naturally an increased usage of SSRIs with long-term tamoxifen treatment to maintain compliance. Unfortunately, the metabolism of tamoxifen to hydroxylated metabolites [141][142][143] and the metabolism of SSRIs [39,[144][145][146][147] both occur via the CYP2D6 gene product. Indeed Stearns and coworkers [97] showed that the SSRI inhibitor paroxetine reduced the levels of endoxifen during adjuvant tamoxifen therapy and endoxifen levels decrease by 64% in women with wild type CYP2D6 enzyme.…”
Section: Tamoxifen Metabolism Todaymentioning
confidence: 99%
“…As mentioned above, fluoxetine is known to inhibit a number of likely RAdegrading CYP450-isozymes 30 . Therefore, a local interaction in the brain may be of relevance for local RA concentrations as well.…”
Section: The Metabolism Of Retinoidsmentioning
confidence: 96%
“…Several specific, but likely "serotonin-independent" effects of fluoxetine have been demonstrated, including enhancement of synaptic plasticity in hippocampal neurons 3,4 , anti-inflammatory mechanisms 5 , but also a serotonin-independent effect on the acid sphingomyelinase-ceramide system 6,7 . Interestingly, one of the hallmark characteristics of fluoxetine is its rather long half-life and its ability to interact strongly with the cytochrome P450 (CYP450)-system 30 . While this fact has mainly been of interest in the context of drug-drug interactions, it is noteworthy that CYP450 enzymes are rather ubiquitously expressed, also (or especially) in the brain, where they are believed to contribute to specific local small molecule levels.…”
Section: Introductionmentioning
confidence: 99%